Sesquiterpene Lactones from Inula hupehensis Inhibit Nitric Oxide Production in RAW264.7 Macrophages - Qin, Jiang-Jiang; Zhu, Jia-Xian; Zeng, Qi; Cheng, Xiang-Rong; Zhang, Shou-De; Jin, Hui-Zi; Zhang, Wei-Dong (Planta Medica, 2012)
Phytochemical investigation of the aerial parts of Inula hupehensis Ling. led to the isolation and identification of 27 sesquiterpene lactones (1–27), including three new eudesmanolides (3–5), three new germacranolides (9–11), one new xanthanolide (16), two new carabrone derivatives (25–26), and 18 known sesquiterpene lactones. The structures were elucidated by extensive spectroscopic methods and comparison to previously reported spectroscopic data. All compounds were evaluated for their inhibitory effects against LPS-induced nitric oxide production in RAW264.7 macrophages, and compound 5 showed the strongest activity with the IC50 value of 3.2 ± 0.4 µM.
Keywords: Inula hupehensis Ling.; Asteraceae; sesquiterpene lactones; nitric oxide production; structure-activity relationships